NUMERICAL EVALUATION BY MODELS OF LOAD AND SPARK TIMING EFFECTS ON THE IN-CYLINDER HEAT TRANSFER OF A SI ENGINE - SAYIN, CENK (TAYLOR & FRANCIS INC, 2009)
The aim of this study is to examine numerically the effects of spark timing and load parameters on the in-cylinder heat transfer of a SI engine by using experimental engine test data. For the investigation, a four-stroke, air-cooled, single-cylinder SI engine was tested at different spark timings and loads at a single engine speed of 2000 rpm. Woschni, Hohenberg, and Han models were employed to estimate the in-cylinder heat transfer coefficient in the case of different test conditions because of being favorable models on the SI engine operations. The evaluations show that the in-cylinder heat transfer characteristics of the air-cooled SI engine strongly depend on the load while they slightly depend on the spark timing.